2022
DOI: 10.3390/ijms23052601
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Specificity, Neurotoxicity, and Possible Involvement of the Nuclear Receptor Response Pathway of 4,6,8-Trimethyl Azulene Amide Derivatives

Abstract: Background: Very few papers covering the anticancer activity of azulenes have been reported, as compared with those of antibacterial and anti-inflammatory activity. This led us to investigate the antitumor potential of fifteen 4,6,8-trimethyl azulene amide derivatives against oral malignant cells. Methods: 4,6,8-Trimethyl azulene amide derivatives were newly synthesized. Anticancer activity was evaluated by tumor-specificity against four human oral squamous cell carcinoma (OSCC) cell lines over three normal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In the studies carried out, it has been observed that Gua has radical scavenging properties, can protect cells against oxidative stress, can be used as an antioxidant and antiproliferative agent, and heals cells with hepatotoxicity [42,43]. In addition, it has been reported that Gua has antiretroviral activity against HIV 1 virus and can be used in anticancer drugs in another study [40,44,45]. Park et al (2021), also stated that Gua showed the significant ABTS+ radical scavenging activity similar to ascorbic acid [46].…”
Section: Discussionmentioning
confidence: 99%
“…In the studies carried out, it has been observed that Gua has radical scavenging properties, can protect cells against oxidative stress, can be used as an antioxidant and antiproliferative agent, and heals cells with hepatotoxicity [42,43]. In addition, it has been reported that Gua has antiretroviral activity against HIV 1 virus and can be used in anticancer drugs in another study [40,44,45]. Park et al (2021), also stated that Gua showed the significant ABTS+ radical scavenging activity similar to ascorbic acid [46].…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that pyoktanin blue (30), 1,5-diaryl-3-oxo-1,4-pentadienes (31), 4,6,8-trimethyl azulene amide derivatives (32), and pyrazole-based hybrids carrying hydrazone and zincbinding benzenesulfonamide pharmacophores (33) showed high tumor selectivity for OSCC, however induced only slight activation of caspase-3 in Ca9-22 cells, suggesting nonapoptotic cell death.…”
Section: Figure 5 Induction Of Accumulation Of Cells To G 2 /M and Su...mentioning
confidence: 99%